2014
DOI: 10.14689/ejer.2014.55.1
|View full text |Cite
|
Sign up to set email alerts
|

Active and Democratic Citizenship Education and its Challenges in Social Studies Classrooms

Abstract: Problem Statement: Turkey's passive and task-oriented approach to citizenship education, which has endured since the Ottoman Empire period, has begun to change into more active and democratic citizenship education since Turkey joined the European Union. Identifying the practical problems as well as describing the challenges when practicing the Social Studies curriculum will contribute to citizenship education and its development, both in Turkey and in similar countries. Purpose of Study:The purpose of the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 170 publications
0
14
1
17
Order By: Relevance
“…In the studies carried out by Ersoy (2014) and Memişoğlu (2014), the results revealed that social studies teachers in Turkey mostly apply teacher centered practices in citizenship education such as direct explanation, question and answer method, and narration techniques, which poses a challenge to the active citizenship education. As Çayır (2002) suggests, an effective citizenship education needs to promote inquiry and action with the aim of creating behavioral and attitudinal changes rather than limiting itself to the cognitive domain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the studies carried out by Ersoy (2014) and Memişoğlu (2014), the results revealed that social studies teachers in Turkey mostly apply teacher centered practices in citizenship education such as direct explanation, question and answer method, and narration techniques, which poses a challenge to the active citizenship education. As Çayır (2002) suggests, an effective citizenship education needs to promote inquiry and action with the aim of creating behavioral and attitudinal changes rather than limiting itself to the cognitive domain.…”
Section: Discussionmentioning
confidence: 99%
“…As Child-to-Child approach encourages the active participation of students in the teaching and learning process by providing them with the opportunity to take actions in the community, students could contribute to the solution of social problems in their school and the community. Several researchers (e.g., Akşit, 2009;Ersoy, 2014;Keser et al, 2011;KaramanKepenekci, 2005;Mısırlı-Özsoy, 2010;Som & Karataş, 2015;Şensoy, 2014;Ülger, 2013) also underline the positive impact of authentic and extra-curricular activities on the development of active citizenship and the promotion of active citizenship values and competencies in Turkish schools. In particular, as Keser et al (2011) argue, these extra-curricular activities enable students to develop an active citizenship perception, social accountability, intercultural awareness, awareness of democracy and human rights, thinking and research skills, and interaction and intrapersonal skills which comply with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a study conducted by Tomul, Celik, and Tas (2012) revealed that according to prospective teachers, in-service teachers behave in a discriminative way in terms of students' socio-economic features, political views and beliefs. In a similar study by Ersoy (2014), it was detected that, since teachers do not have adequate knowledge and experience concerning effective and democratic citizenship education, primary students belonging to lower socio-economic levels cannot exercise their rights adequately compared to those who come from higher socio-economic levels. Thomas (2007) in his study argues that teachers who intend to maintain social justice implementations are not supported enough.…”
Section: Introductionmentioning
confidence: 99%